Life history of frogs of the Brazilian semi‐arid (Caatinga), with emphasis in aestivation. (20th March 2019) - Jared, Carlos; Mailho‐Fontana, Pedro Luiz; Mendelson, Joseph; Antoniazzi, Marta Maria
Abstract: The semi‐arid region (Caatinga), that corresponds to 18.26% (1, 540, 000 km 2 ) of Brazil, occupies most the northeast region. Rainfall is irregular and concentrated within the first 3 months of the year. Prolonged periods of drought, with low total rainfall, may extend for two or more years. Most of the rivers of this biome are temporary, remaining totally dry during periods of drought. We collected and observed the natural history and biology of the species Proceratophrys cristiceps, Pleurodema diplolister and Physalaemus spp, both in the rainy and dry seasons, in ten field expeditions to the State of Rio Grande do Norte (Brazil). We focused on the morphology of the skin and cutaneous glands, specifically in their defence against desiccation. During the dry season, they form concentrations in the bed of temporary rivers, burrowing themselves in favourable locations within the sand, at depths that may exceed 1.50 m. No morphological evidence was found that there are specific cutaneous adaptations against water loss. We suggest that the cutaneous fragility per se is a cutaneous adaptation to water balance. The behaviour of such anuran species, together with their physiological characteristics, should be the main tools to face the challenge of living in xeric conditions.